2005
DOI: 10.1177/0022002704272829
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Logit Estimation of Radical Islamic Terrorism in Europe and North America

Abstract: This article estimates what characteristics (e.g., location, number of casualties, and type of attack) are associated with an Islamic terrorist attack. This is established by identifying the significant determinants of the probability that an attack had been carried out by Islamic terrorists. For Europe, the United States, and Canada, the analysis employs ITERATE (International Terrorism: Attributes of Terrorist Events) data from October 1979 to December 2002 to ascertain the significant characteristics of Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Moreover, on analyzing Basque market-listed companies in comparison with non-Basque listed companies, they concluded that the former show a negative performance as an externality of terrorism. Barros and Proença (2005) Time series analysis is also used to analyze generic characteristics of terrorist attacks. Enders and Sandler (2002) analyzed the pattern of transnational terrorism with a Fourier model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, on analyzing Basque market-listed companies in comparison with non-Basque listed companies, they concluded that the former show a negative performance as an externality of terrorism. Barros and Proença (2005) Time series analysis is also used to analyze generic characteristics of terrorist attacks. Enders and Sandler (2002) analyzed the pattern of transnational terrorism with a Fourier model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The degree of effects may be statistically measured by the use of standard deviations from the mean.Terrorist attacks are a good example of events whose seriousness is in large part a consequence of the size of their potential effects. Although the incidence of attacks is capable of being modelled (Enders and Sandler 2002, Tavares 2004, Enders and Sandler 2006 and has also, overall, been in decline worldwide since the early 1990s Sandler 2002, Sandler andEnders 2004), the scale of the largest individual attacks has been increasing and the type and scale of attacks differ widely from year to year (Tilly 2004, Tavares 2004) and between terrorist organizations (Tilly 2004, Barros andProença 2005). 8.…”
Section: 11risk Identification and Categorization Of Port And Parmentioning
confidence: 99%
“…Such terrorist attacks are anticipated to have more indiscriminate killings and U.S. targets. The Barros and Proença (2005) article investigates the characteristics that distinguish Islamic from other terrorist attacks. Using ITERATE data from October 1979 to December 2002, the authors create a dependent variable indicating whether the terrorist incident is by a radical Islamic group.…”
Section: Special Issue Articlesmentioning
confidence: 99%